Increasing Student Learning Motivation In PE Subjects ThroughClass V Demonstration Learning Method At SD Negeri 10 Seluma - Agustin, Feby Veronicha; Sumantri , Ajis; Juwita, Juwita (Universitas Dehasen Bengkulu, 2025)
The results of research in cycle I and cycle II, it can be concluded that the use of guided learning methods and demonstrations in learning PE material for big ball games for class V students of SD Negeri 10 Seluma can increase student enthusiasm and the learning atmosphere becomes enjoyable, because students feel given guidance and direction at every stage of learning, so that student activity in participating in learning big ball games becomes better. Increasing student learning completeness with the number of students completed in cycle I 14 students (SS = 40.6%, STS = 17.9%) in cycle II 14 students (SS = 19.1%, STS = 6.1%) from a total of 19 students in the learning process of big ball games through guided learning methods and demonstrations, so that there is an increase in learning provisions from cycle I and cycle II.